SOME RISK FACTORS OF IRON DEFICIENCY ANEMIA AMONG CHILDREN AGED 2 TO 60 MONTHS AT THE PEDIATRIC DEPARTMENT, CAO BANG PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze several risk factors associated with iron deficiency anemia among children aged 2 to 60 months treated at the Pediatric Department, Cao Bang provincial General Hospital.Method: A case-control study was conducted including 108 children diagnosed with iron deficiency anemia and 216 non-anemic controls.Results: Children with moderate and severe stunting had a significantly higher risk of iron deficiency anemia, being 7.81 and 21.98 times more likely to develop anemia compared to those with normal nutritional status (95% CI: 1.44-42.37; p = 0.017 and 95% CI: 1.60-301.85; p = 0.021, respectively). Preterm had a 5.16-fold higher risk of iron deficiency anemia compared to full-term children (5.16; 95% CI: 1.77-15.03; p = 0.003). Infants whose mothers were under 20 and over 35 years of age had a 3.69 times higher risk of iron deficiency anemia than the other group (95% CI: 1.42-9.57; p = 0.007). Proper nutritional practices served as protective factors against iron deficiency anemia, including timely introduction of complementary foods and maintaining a diversified diet, which significantly reduced the risk of iron deficiency anemia.Conclusion: Moderate and severe stunting and preterm birth significantly increase the risk of iron deficiency anemia in children. Appropriate feeding practices, such as timely and diverse complementary feeding, play a protective role against iron deficiency anemia.
Keywords: Anemia, iron deficiency, children, Cao Bang.